Distribution of Cadmium in Fresh Vegetables Marketed in Southeast China and Its Dietary Exposure Assessment - Xiao-Dong Pan; Jian-Long Han (Foods, 2023)
This study investigated concentrations of cadmium (Cd) in 2465 vegetable samples (52 species) from 2018 to 2022 and estimated the associated health risk for local consumers. The average concentration of Cd was 0.035 mg kg−1, and the percentage of samples exceeding the Chinese maximum allowed concentration was 3.89% (96/2465). The top five species with highest Cd levels were Lilium brownii F (0.182 mg kg−1), Allium chinense G (0.117 mg kg−1), Allium macrostemon Bunge (0.105 mg kg−1), Colocasia esculenta (0.064 mg kg−1), and Amaranthus tricolor L (0.054 mg kg−1). Bulb vegetables had a higher relative accumulation of Cd compared to other vegetables. The levels of Cd in vegetables varied significantly across sampling areas and years. The mean estimated daily intake (EDI) of cadmium through consumption of vegetables was 0.519 μg kg−1 bw per day for adults and 0.217 μg kg−1 bw per day for children. The target hazard quotients (THQs) were all less than the threshold of 1 for both adults and children. This indicates that there is low health risk for Cd through vegetable consumption. However, routine monitoring of Cd levels in food is still crucial to ensure food safety and protect public health.